The repercussions of Covid-19 pandemic on the labour force participation of older people: a narrative literature review - Chang Foo Chung; Tan Sharon; Jennyca Singau; Khairul Hanim Pazim; Kasim Mansur (Universiti Malaysia Sabah, 2020)
In 2002, the World Health Organisation (WHO) designed a framework for active ageing society which was implemented by most of the countries in the world to date. Many studies cited that the labour force participation of older people is one of the key factors in promoting the concept of active ageing (Punyakaew et al., 2019; Halaweh et al., 2018). Due to an unexpected disastrous COVID-19 pandemic emerged, there is a need to revisit the possible effects of this pandemic on the labour force participation of the older population. As of 9 October 2020, WHO reported that there are more than 36 million infected people and 1,056,186 deaths in 216 countries worldwide and the numbers are still rising at a rapid rate. Older people were identified as one of the most vulnerable groups to COVID-19 virus. It is expected that the current situation is less favourable to older people in Malaysia not only to their participation in the labour market, but in many aspects as well. This paper aims to provide a narrative literature review on how COVID-19 pandemic might have changed the decision of older people in participating in the labour force in Malaysia.